Synthesis, spectroscopic characterization and theoretical calculations of ClF2CC(O)NPCl3 ([chloro(difluor)acetyl]phosphorimidic trichloride) - Iriarte, Ana Graciela (2013)
The synthesis of [chloro(difluor)acetyl]phosphorimidic trichloride (ClF2CC(O)NPCl3), together with a tentative assignment of the vibrational, NMR and mass spectra, are reported. Quantum chemical calculations (MP2 and B3LYP methods with 6-311+G(d) and 6-311+G(2df,p) basis sets) predict three stable conformers in the gas phase (syn, gauche and anti, defined according to the rotation around both the ClCCN and the CCNP dihedral angles). However, only a single C1 symmetry conformer is observed in the liquid phase, possessing the CO double bond in synperiplanar orientation with respect to the PN double bond, and the ClC bond distorted from the plane defined by the CC(O)NP entity. A Natural Bond Orbital (NBO) analysis was carried out for the title compound and related molecules in order to provide an explanation about the electronic properties.